2017
DOI: 10.1161/circoutcomes.116.003532
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Living in Food Deserts and Cardiovascular Risk

Abstract: Background Food deserts (FD), neighborhoods defined as low-income areas with low access to healthy food, are a public health concern. We evaluated the impact of living in FD on cardiovascular risk factors and subclinical cardiovascular disease (CVD) with the hypothesis that people living in FD will have an unfavorable CVD risk profile. We further assessed whether the impact of FD on these measures is driven by area income, individual household income or area access to healthy food. Methods and Results We stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 55 publications
1
62
1
Order By: Relevance
“…Socioeconomic factors are an important risk factor for cardiovascular disease (CVD) and a major obstacle to implementing lifestyle modifications for stroke prevention. Low-income areas and low individual household incomes were found to be independent predictors of a higher 10-year risk for CVD [ 12 ]. Even in high-income countries that have seen reductions in overall stroke risk in recent years, inequality gaps were not bridged.…”
Section: Lifestyle Modificationsmentioning
confidence: 99%
“…Socioeconomic factors are an important risk factor for cardiovascular disease (CVD) and a major obstacle to implementing lifestyle modifications for stroke prevention. Low-income areas and low individual household incomes were found to be independent predictors of a higher 10-year risk for CVD [ 12 ]. Even in high-income countries that have seen reductions in overall stroke risk in recent years, inequality gaps were not bridged.…”
Section: Lifestyle Modificationsmentioning
confidence: 99%
“…Specifically, state-level minimum wage policies could influence the individual-level income of lower-wage workers, thereby impacting access to heart disease prevention and treatment (Mensah, 2005). Socioeconomic status as measured by income and/or education has been associated with the risk of heart disease among adults (Franks et al, 2011; Kaplan and Keil, 1993; Kelli et al, 2017). …”
Section: Introductionmentioning
confidence: 99%
“…This study enhances our knowledge regarding the association of area-level factors and cardiometabolic risk factors. Prior studies have consistently found that adverse area-level factors, such as poverty, are associated with increased cardiometabolic risk, even when adjusting for individual-level factors, such as income 2 27–29. However, we did not know whether the presence of area resources that might plausibly support health, such as food and nutrition resources, would be associated with lower cardiometabolic risk.…”
Section: Discussionmentioning
confidence: 74%